DETERMINASI KETEPATWAKTUAN PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BEI - Rosdianti Br Regar, Novi; Putri, Annie Mustika; Ramashar, Wira (LPPM Universitas Bina Bangsa, 2024)
The importance of submitting annual financial reports on time greatly influences the quality of the financial reports themselves. Financial reports are said to be of quality when the information is presented in a timely manner and is available when needed. Timeliness means that information must be delivered as quickly as possible so that it can be used as a basis to assist in decision making. This research was conducted to see whether or not there was an influence from the variables, namely profitability, leverage, liquidity, company size and audit opinion. This research was conducted on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2021-2022. Sampling used purposive sampling technique with a total of 52 samples. The data used is secondary data. The data analysis technique used is logistic regression analysis. This research analyzes using SPSS version 26. The research results show that profitability has no effect on the timeliness of financial reporting. Meanwhile, leverage, liquidity, company size and audit opinion influence the timeliness of financial reporting